Impact of isolation measures due to the COVID-19 pandemic on rapid HIV tests in an Acute General Hospital in Buenos Aires City (Actualizaciones en Sida e Infectología, 2022)
INTRODUCTION: HIV infection remains as a public health worldwide problem. The restrictions taken during the COVID-19 pandemic could have affected the scope of the 90-90-90 goals proposed by UNAIDS. The aim of this work is to determine the impact of the COVID-19 pandemic on the performance of rapid HIV tests in an Acute General Hospital.METHODS: Retrospective analysis of data from patients over 16 years old, of both sexes, who underwent a rapid HIV test during the COVID-19 pandemic vs. the previous period.RESULTS: Of 611 tests, 473 (77.4%) correspond to the pre-pandemic period and 138 (22.6%) to the pandemic. The median age (interquartile range) was 32 years old (24-40); male sex 386 (63.2%), without significant differences. During the pre-pandemic vs pandemic period, the reasons for testing were: health control 47.6% (n=225) and risk situations/symptoms 52.4% (n=248), vs 27.5% (n= 38) and 72.5% (n=100) respectively, p=0.0001. Positive tests: 5.7% (n=27) vs 8.7% (n=12), p=0.28. The median CD4+ T lymphocyte count and viral load were: 327 cells/uL (135-718) and 66,300 copies/mL (5,260-192,000), with no significant differences.CONCLUSIONS: The number of tests carried out during the pandemic equals to a third of those performed during the previous period, with a decrease in those motivated by health controls; evidencing the impact of the pandemic on the diagnosis of HIV.
Keywords: HIV; COVID-19; Pandemics; Diagnosis